Application of Artificial Intelligence in Smart Cities: Current Status, Challenges and Future Trends - Yao, Yao (International Journal of Computer Science and Information Technology, 2024)
The application of artificial intelligence (AI) in smart cities represents a significant advancement in urban development, aiming to enhance efficiency, sustainability, and the overall quality of life for residents. This paper provides an extensive analysis of the current status, challenges, and future trends associated with the application of AI in smart cities. Firstly, it examines the current status, highlighting the diverse applications of AI in smart city initiatives, such as traffic management, public safety, energy optimization, and environmental monitoring. These applications have demonstrated promising results in improving urban operations and resource allocation. Secondly, it delves into the challenges faced, including data privacy concerns, ethical implications, and the need for robust infrastructure to support AI-driven systems in urban environments. Overcoming these challenges is essential to ensure the responsible and effective deployment of AI technologies in smart cities. Lastly, the paper discusses future trends, emphasizing the potential for AI to drive innovation in areas such as autonomous transportation, predictive maintenance, and citizen-oriented services. By examining the opportunities offered by AI in smart cities, this research aims to provide insights into the transformative impact of AI on urban living and governance, contributing to the sustainable development of smart cities.